Design, Simulation, and Performance Analysis of X-Band Patch Array Antenna for Car-Speed Detection Radar - Lasisi, Hammed Oyebamiji; Ogungbayi, Peter Ropo; Asafa, Mubarak Oluwafemi (Journal of Science and Technology, 2025)
The antenna is an essential component that plays important role in radar target detection and parameter estimation. This paper presents the design and simulation analysis of X-band patch array antenna for car-speed detection and monitoring radar system. A patch array antenna was designed at a center operating frequency of 10 GHz. The designed patch array antenna was simulated with a Computer Simulation Technology (CST) Microwave-Studio to analyze the antenna radiation pattern and other broadband properties. A compact and light-weight X-band 4×4 patch array antenna was realized on RT/Duroid 5880 copper board with 1.6 mm thickness and dielectric constant of 2.2. The patch array antenna shows high gain and good radiation characteristics with a simulated gain of 19.35 dBi, and corresponding radiation efficiency of 89.02%. The fabricated antenna was experimentally characterized and tested for real-world car-speed detection radar system. The studied patch array antenna demonstrates impressive performance suitable for radar applications.